Identification Of Effective Technique To Estimate Water Loss In Water Supply Scheme A Case Study Of Usm Engineering Campus - Azmi, Aniq Syahmi (Universiti Sains Malaysia, 2022)
Water distribution networks may see significant savings from reducing nonrevenue water (NRW). The majority tends to concentrate on the design and implementation aspects of reducing NRW loss by better controlling leaks, reservoir overflows, and water theft. In contrast, choices about repairing or modernisation a water network should be made after examining water losses. The study aims to identify the possible cause of water loss and compare water losses in water bill systems over five years. The compared networks share several characteristics, such as the water intensity indicator value. The analysis results were performed to determine the percentage rate of water loss in five years. Analysis was done using IWArecommended water losses indices, such as Non-Revenue Water Level (NRWL); Geometrical Increase Method was used to determine the future increment in population and predict the water loss in the future. In many countries, including Malaysia, the IWA-recommended approach is becoming increasingly popular. According to the results, water losses in both systems are less than those found in the data for other networks of a similar type in the literature.